Rancang Bangun Aplikasi 3D Spare Part Sepeda Motor Untuk Pembelajaran Teknik Otomotif(Studi Kasus di SMK Adi Sumarmo) - KUSUMO, AUFA ANGGUN PROBO; , Umi Fadlilah, S.T., M.Eng (2017)
Augmented Technology is technology capable of being used for knowledge, learning, and game. Based on great rewards this is writers developing an application based augmented as a media learning students Adi Sumarmo with 3D for the introduction of spare parts a motorcycle. Learning that theory motorcycle still in teaching usual, that require visual development of learning to facilitate understand that a motorcycle part. An author in do research uses the observation, interview, research, analysis, planning, design, testing, and implementation. Software used is Unity, Solid Work, Blender, Vuforia, SDK, CorelDraw, and Audacity. The results of the study of learning based the android application. Learning has been implemented in smk adi sumarmo karanganyar. Testing functionality also have been done by teachers and students. Tests carried out in terms of the success of application work. System learning augmented reality can be an impact better for increase the quality of education. Expected application that has been created can continue to be used in order to support their experiences in the smk adi sumarmo karanganyar